FAKTOR-FAKTOR MEMENGARUHI NIAT MAHASISWA MEMPELAJARI SISTEM INFORMASI MANAJEMEN KEUANGAN BERBASIS THEORY OF PLANNED BEHAVIOR - Lea Christanti, Paramita; Sri Nugroho, Arif Julianto; Setyawanti, Dandang; Marjukah, Anis; Santoso, Agus; Purnomo, Harri; Prakosa, Cucut (Journal of Computer Science and Technology (JCS-TECH), 2025)
This research aimed to test whether the learning model obtained by Financial Management Information System (MIS) intention can strengthen attitude variables, subjective norms and self-efficacy control of Unwidha undergraduate students’ interest. The research design was carried out using quantitative methods that explained the causal relationship between one variable and the other variables to be tested. The hypothesis test was formulated in a model using the Structural Equation Model multivariate test. The population in this research are all FEP Unwidha undergraduate students who have a strong interest in Financial MISp. The sampling technique was carried out by purposive sampling of 120 student respondents. The results of the analysis found that financial MIS influences three variables and the overall model in the SEM fit test. The research results can serve as a basis for making quality financial MIS learning problem-based models by adding aspects of real financial MIS practice for Unwidha undergraduate students